2021
DOI: 10.1371/journal.pone.0251259
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle-enriched miRNA profiles across pregnancy in the MADRES cohort

Abstract: MicroRNA (miRNA) circulating in plasma have been proposed as biomarkers for a variety of conditions and diseases, including complications during pregnancy. During pregnancy, about 15–25% of maternal plasma exosomes, a small size-class of EVs, are hypothesized to originate in the placenta, and may play a role in communication between the fetus and mother. However, few studies have addressed changes in miRNA over the course of pregnancy with repeated measures, nor focused on diverse populations. We describe chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 84 publications
(102 reference statements)
1
8
0
Order By: Relevance
“…Foley et al explored maternal plasma exosomes during pregnancy, unveiling alterations in miRNA profiles, particularly related to energetic and metabolic processes, in both early and late pregnancy. These findings significantly contribute to understanding the mechanisms supporting a healthy pregnancy [26]. Gródecka-Szwajkiewicz et al investigated angiogenic factors and miRNAs in umbilical cord blood, distinguishing between preterm and term newborns.…”
Section: Resultsmentioning
confidence: 99%
“…Foley et al explored maternal plasma exosomes during pregnancy, unveiling alterations in miRNA profiles, particularly related to energetic and metabolic processes, in both early and late pregnancy. These findings significantly contribute to understanding the mechanisms supporting a healthy pregnancy [26]. Gródecka-Szwajkiewicz et al investigated angiogenic factors and miRNAs in umbilical cord blood, distinguishing between preterm and term newborns.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, miR-222 and miR-146a were investigated, two potential biomarkers that are responsive to PM exposure in adults [ 39 , 40 , 41 , 42 ]. The selected methods included commercial kits and assays which were successfully used in previous studies involving other biofluids, such as blood and sweat [ 68 , 69 ]. The results of our study confirmed the rationale of using EVs in saliva as a source for investigating specific extracellular miRNAs as biomarkers of air pollution exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Mice expressing either the ectopic human C19MC paternalimprinted cluster [119] or with a knockout of the maternalimprinted C14MC cluster [120] show increased placental growth [121]. A number of studies have suggested that these miRNAs may be present in EVs released by the placenta and that levels increase in maternal blood during pregnancy, before decreasing following birth [122][123][124][125][126]. They have also been detected in umbilical cord blood, suggesting communication from placenta to foetus [127].…”
Section: Human Leukocyte Antigen-g (Hla-g)mentioning
confidence: 99%